The Effect of Spiritual Counseling and Hope Therapy Training on Palliative Care Self-efficacy of Nursing Students of Urmia Azad University. - Elahe Radman; Monireh Rezaee; Esfandyar Baljani (Hamadan University of Medical Sciences, 2021)
Introduction: Palliative care is of great importance for improving the quality of life of chronic patients and providing palliative care education to nurses is one of the important ways in the development of such care. The purpose of this study was to determine the effect of spiritual counseling and hope therapy on self-efficacy of palliative care of nursing students. Methods: This was an experimental study. The statistical population consisted of senior nursing students of Urmia Azad University, Urmia, Iran. The samples were selected from the complete list of students using census sampling and then divided into intervention and control groups. Data were collected using a two-part questionnaire including demographic information and clinical practice self-efficacy questionnaire. The intervention group received 9 sessions of training on hope and spiritual counseling but the intervention group did not receive training. The intervention results were re-gathered after 9 sessions using the same questionnaire. Results: Independent-sample t-test showed that the mean scores of overall clinical self-efficacy scores of nursing students before spiritual counseling and hope therapy were not significantly different (P>0.05), while the same test showed that there was a significant difference between the mean scores of clinical self-efficacy between intervention and control groups after spiritual counseling and hope therapy program (t=63.6, P=0.02). Conclusion: The results of this study showed that spiritual counseling and hope therapy training is effective on self-efficacy of palliative care of nursing students and can be used in palliative care teaching and pattern-based nursing care for a variety of patients.